The Strategy of Institutional Collaboration to Expedite The Recognition of Customary Law Communities Through Land Registration in Aceh Besar, Indonesia - Sulaiman, Sulaiman; Abdullah, Muhammad Adli; Wulandari, Mitra; Mansur, Teuku Muttaqin; Sautunnida, Lia (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2025)
The recognition of Indigenous Law Communities (Masyarakat Hukum Adat/MHA) involves a complex and multi-layered process. This article aims to analyze strategies for accelerating the recognition of MHA through the registration of customary land in Aceh Besar Regency. This research employs a qualitative methodology, with primary data obtained through fieldwork, preceded by a customary land survey, and complemented by legal materials. The analysis was conducted using a qualitative approach.The findings indicate that customary land continues to exist in Aceh Besar, covering an area of approximately 4,593.78 hectares, according to the survey. While this land holds potential for registration, the formal verification process remains challenging. The registration of such lands must be carried out at the Land Office—a regional branch of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN)—and requires the official designation of legal subjects by the Aceh Besar Regency Government.The study further emphasizes the intricacies of recognizing MHA, which require verification of both the subject (i.e., the community’s legal status as MHA) and the object (i.e., the land claimed). One viable strategy to accelerate the recognition process is through institutional collaboration—integrating the object recognition process under the Land Office with the subject designation process handled by the regency government. This approach can be facilitated by forming a joint working structure based on submitted applications. Such a collaborative framework would improve communication and streamline policy decisions, enabling more efficient and effective recognition of both the MHA and the registration of their customary land.